2006
DOI: 10.1111/j.1478-3231.2006.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular adsorbent recirculating system treatment for patients with liver failure: the Hong Kong experience

Abstract: Our results indicated that MARS can effectively improve serum biochemistry and is suitable for temporarily supporting patients with liver failure where transplantation is not immediately available. There is, however, no clear evidence showing that MARS can increase survival, improve the chance of transplantation or assist liver regeneration. Future studies in the form of randomized-controlled trials are crucial to characterize the true potential of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…137 The severity of the PHLF should be followed using laboratory values such as INR, platelets, ammonia, bilirubin, and creatinine. Resuscitative measures and organ support provide the optimal environment for liver regeneration.…”
Section: Treatment Of Post-hepatectomy Liver Failurementioning
confidence: 99%
“…137 The severity of the PHLF should be followed using laboratory values such as INR, platelets, ammonia, bilirubin, and creatinine. Resuscitative measures and organ support provide the optimal environment for liver regeneration.…”
Section: Treatment Of Post-hepatectomy Liver Failurementioning
confidence: 99%
“…But only one patient survived. Also a study from Hong Kong Hospitals showed a poor outcome in patients with PHLF and MARS therapy despite of improvement in biochemical parameters [33]. …”
Section: Treatment Of Phlf Remains Difficultmentioning
confidence: 99%
“…Large, randomized, controlled trials did, however, fail to demonstrate a statistically significant survival benefit 14, 15. In the PHLF situation, only a few single‐center experiences have addressed the use of MARS as a rescue treatment option,16, 17, 18, 19, 20 and all of them suffer from heterogeneous patient groups and a lack of standardized treatment protocols. Recently, we reported our retrospective experience with MARS for PHLF at two tertiary referral centers where we found a trend toward improved 90‐day and long‐term survival in patients who received several MARS treatments early in the postoperative course 21.…”
Section: Introductionmentioning
confidence: 99%